Satisfaction in terms of autonomy, competence and relatedness, and its importance in promoting job motivation in the Portuguese culture - Costa, Diogo Patricio Varandas da (2015)
Self-Determination Theory (SDT) argues that autonomy, competence and relatedness are three universally critical needs that, once satisfied, will promote self-determined types of motivation and more intrinscally motivated behaviours that yield positive effects on well-being. In contrast, researchers on cross-cultural differences argue that the pursuit of autonomy and relatedness in collectivist cultures is not compatible. For individuals living in collectivist cultures valuing social bonding, striving for autonomy would be in conflict with the development of meaningful and satisfying relationships. The present study explored the role of the three needs in fostering self-determined types of job motivation in the Portuguese culture. We hypothesized that relatedness would have a stronger impact than autonomy and competence, in promoting self-determined types of motivation at the work place. Consistent with SDT, we also hypothesized that an interaction between autonomy and relatedness would have significant results in enhancing self-determined types of job motivation. Both of our hypothesis were not supported by the data. Instead, the results show that, even in the Portuguese collectivist culture, autonomy and competence are the most significant basic needs predicting self-determined types of job motivation, only partially supporting SDT’s claims.